NASA resilience and leadership: examining the phenomenon of awe - Thompson, Jeff (Frontiers in Psychology, 2023)
This study examines how a phenomenon, awe, along with related resilience practices, is perceived by a NASA medical and mental health professional, who also serves in a leadership role, and how awe has impacted their work and personal life. Considering both their leadership role and how their work involves supporting the wellbeing of astronauts pre-mission, during missions, and post-mission, the potential impact of awe on the NASA expert has individual implications along with many others, especially in stressful environments. The results indicate that reflecting on awe experiences can support a person finding meaning and purpose in their life, evoke gratitude, increase social connectedness, promote optimism and other resilience skills in the moment, and generally have a sustainable positive effect.